Investigating the Significant Role of YouTube as an Educational Tool in Developing Learners’ Self-determination: A case of EFL Students at Adıyaman University - Boucif, Fatima (My University, 2023)
The online video-sharing platform, YouTube.com, has been coded as today's mainstream media among youth. YouTube is a free service and can be a great online space for today's young generation to discover or search for things they like. From a theoretical point of view, many teachers and scholars believe that English is a dominant language in which much of the content can be found and understood. This fact encourages and motivates them to switch from traditio nal teaching to modern one to create joyful, prosperous, and academic content in online spaces to help learners develop their skills in learning English autonomously. From this perspective, this research study aims to investigate the use of YouTube and its crucial role in increasing university learners' self-determination. It brings some benefits to the field of English learning. To uphold this study with more valid data, we used a questionnaire as an appropriate research tool for students to investigate their perspective and attitude toward incorporating YouTube videos out of the classroom setting to develop students' autonomy. Our participants were third-year licence students in the English language department. The findings showed that using YouTube videos as motivational materials facilitate the students' English learning and develop their self-determination. Therefore, this research study confirms the significant role of YouTube in increasing learners' academic progress depending on their self-reliance, which is vital in language learning motivation and individual performance.
Keywords: Online video-sharing platform; language learning; learner’s autonomy; learner’s Motivation; YouTube